Prediposisi Partisipasi Masyarakat dalam Perencanaan Kampung Wisata (Studi Kasus Kampung Santan) - Sutrisno (FP UMY, 2016)
Prediposisi Partisipasi Masyarakat dalam Perencanaan Kampung Wisata (Studi Kasus Kampung Santan)